AKTUALISASI DIRI DAN MEDIA SOSIAL (DRAMATURGI KAUM MILENIAL DALAM MEDIA SOSIAL TIKTOK): AKTUALISASI DIRI DAN MEDIA SOSIAL (DRAMATURGI KAUM MILENIAL DALAM MEDIA SOSIAL TIKTOK) - Ida Ayu Nyoman Sutriani Dayuoman (UHN IGB Sugriwa Denpasar, 2022)
This study questions the dramaturgy of millennials in Mataram City in the Tiktok social media space. This research is designed in qualitative research with a phenomenological model. The purpose of this research is to conduct scientific studies to contribute ideas to the development of science, especially in the field of communication science. Data collection techniques applied in this study are observation, interviews, and documentation. The research data were analyzed by data reduction techniques, data presentation, and conclusion drawing. To simplify the analysis process, Erving Goffman's Dramaturgy theory is used. Based on the results of the study, it was found that it was important that the presence of TikTok as a popular social media platform among millennials in Mataram City became a means of self-actualization in building self-existence. Aware of self-assessment through social media, the account owners carry out management construction to display the image or picture in another version. This is done for specific goals and objectives to be achieved. TikTok social media allows users to show a picture of themselves as desired but react to the impression displayed by the public. On TikTok social media, the front stage, which is the actor's area in constructing impression management, and the backstage, the scope of ​​the actor who describes his actual situation, can be presented simultaneously.